(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The analogies of the great three poets (Jareer, al-Firazdaq and al-Akhtall) are considered to be from the wonders of the Umayyad Poetry. The authors, critics and fans of this poetry used to consider these wonders as privileged poetic texts. This type of poetry had its own great value due to its linguistic record as many words and expressive images of the Arabic language are mentioned in its writings, besides echoing that life which is gone away and absent along with what has been lost from the rich history, ancestry and precious days of Arabs. The analogies were nearly like drama in terms of the poetic story material reflected form day events. No doubt the audience of al- Marbid and al-Kunasa admired them and are interested in following up this art and its creating the different meanings related to the glories and heroes of the tribe as well as following up the ironic images which allow analogy poets to prove wonderful abilities in drawing and imaging whether eminent in boasting or degrading in satire. On the other hand, the analogical texts are like the dramatic scenes which each one on its own is considered a building block in art presented by the poet. The study clarifies the structure of the ruin-communion scene in Jareer’s and al-Firazdaq’s analogies and its active function to achieve the desirable aims of the poet from them, including the direct analogy in raising someone’s position, emphasizing values in boasting or depreciating the value of the opponent and attacking him in satire, or the indirect analogy in entertaining and enjoying the audience. Thus, reading this research accurately answers many questions regarding: how the two poets built the analogical scene, to what extent they could free their way of writing from the traditional artistic structure of a ruin-communion scene in the poem besides implying the scene with preluding functions for the original topic, and what role of the poet’s literary attitude has in composing such scenes, implying suggestive and indicative meanings to become an important functional factor in the artistic structure of analogies.